Development of Emotional Intelligence by Art-Therapy Means (Journal of Educational Sciences, 2017)
The article deals with the concepts of “emotional intelligence” and “art therapy”. Based on the theories analysis, the theoretical bases for the development of emotional intelligence are systematized. The following principles of emotional intelligence development are singled out: awareness of emotions, self-awareness, “here and now”, exit from the comfort zone, constant feedback. Based on the analysis of the theories of emotional intelligence and art therapy, three components of emotional intelligence are distinguished: motivational, cognitive, emotional-technological. A model for developing the emotional intelligence of schoolchildren through art therapy has been developed. The structural model of the emotional intelligence development of schoolchildren through art therapy consists of targeted, meaningful, programmatic, instrumental and resultative components and reveals the purpose, objectives, content, principles, as well as the program, forms, means and methods of developing emotional intelligence. For the experimental and pedagogical work, a program of training the development of the emotional intelligence of schoolchildren through art therapy has been developed. The training program was tested on the basis of school No. 55 in Almaty for pupils of 8 classes. In a practical study, 90 schoolchildren took part.Key words: emotional intelligence, art therapy, art technology, creativity, emotions.